2016
DOI: 10.1515/amm-2016-0064
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of Hot-Deformed Cu-3Ti Alloy

Abstract: In the paper, results of investigations regarding temperature and strain rate effects on hot-deformed Cu-3Ti alloy microstructure are presented. Evaluation of the alloy microstructure was performed with the use of a Gleeble HDS-V40 thermal-mechanical simulator on samples subjected to uniaxial hot compression within 700 to 900ºC and at the strain rate of 0.1, 1.0 or 10.0 s -1 until 70% (1.2) strain. It was found that within the analyzed temperature and strain rate ranges, the alloy deformation led to partial or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…For the subsequent samples deformed at higher temperatures in the range from 800 °C to 1000 °C, it was found that the only process controlling strain strengthening in the entire temperature range of plastic deformation was dynamic recovery. So far, the elastomeric tests were only performed for the Cu 3 Ti alloys [ 22 ] and for the CuNiAl [ 23 ] alloys, therefore the results of the elastomeric tests of the CuNi2Si alloy will extend this knowledge.…”
Section: Resultsmentioning
confidence: 99%
“…For the subsequent samples deformed at higher temperatures in the range from 800 °C to 1000 °C, it was found that the only process controlling strain strengthening in the entire temperature range of plastic deformation was dynamic recovery. So far, the elastomeric tests were only performed for the Cu 3 Ti alloys [ 22 ] and for the CuNiAl [ 23 ] alloys, therefore the results of the elastomeric tests of the CuNi2Si alloy will extend this knowledge.…”
Section: Resultsmentioning
confidence: 99%
“…To save energy in production, pressureless solid-state-sintered SiC using several sources of boron and carbon as the boron-carbon additive systems sintered at 1900℃ to 2050℃ have been reported [5,6]. The majority of boron can form solid solutions in the SiC grains, and carbon is used to remove silica (SiO2) layers on the SiC surfaces, the boron-carbon additive system has already been shown to be effective for enhancing densification progress [3,5,7]. Prochazka produced 96% relative density of SiC ceramic with additions of 0.5 wt% boron and 1 wt% carbon after sintering at 2050℃ to 2150℃ in an argon atmosphere [8].…”
Section: Introductionmentioning
confidence: 99%